Conflict Resolution Strategy In Papua Through Concurrent Military and Non-Military Operations Executed By The Indonesian National Armed Forces (TNI) - Arief Fahmi Lubis (International Journal of Law, Crime and Justice, 2024)
Examined through the prism of national security, the imperative emerges for the Indonesian National Armed Forces (TNI) to play a central role in addressing conflicts in Papua, harmonizing effectively with their fundamental mission of promoting the well-being of the local populace. This study aims to establish that achieving resolution in Papua necessitates the implementation of two parallel approaches. In this study, the researcher employs a qualitative method with a descriptive approach. The data is systematically, factually, and expeditiously collected following the contextual conditions prevalent during the research period. The findings underscore the viability of conflict resolution in Papua through the dual avenues of military operations for war and military operations other than war, both executed by the TNI soldiers.